Estrogen reduces atherosclerotic lesion development in apolipoprotein E-deficient mice. - Bourassa, P A (1996)
We have studied the effects of endogenous and exogenous estrogen on atherosclerotic lesions in apolipoprotein E-deficient mice. Female mice ovariectomized (OVX) at weaning displayed increases (P < 0.01) in fatty streak lesions in the proximal aorta and aortic sinus compared with female mice with intact ovarian function. These differences between the OVX and sham controls were apparent in both chow- and "Western-type" diet-fed mice. Moreover, increases in lesion size following OVX occurred without changes in plasma cholesterol. Hormone replacement with subdermal 17-beta-estradiol pellets releasing either 6, 14, or 28 micrograms/day significantly decreased (P < 0.001) atherosclerotic lesion area in both male and OVX female mice. In contrast, neither 17-alpha-estradiol (28 micrograms/day) or tamoxifen (85 micrograms/day) affected lesion progression in OVX female mice. In the Western diet-fed group, exogenous estradiol markedly reduced plasma cholesterol and triglycerides, whereas, in animals fed the chow diet, exogenous estrogen and tamoxifen treatment only decreased plasma and very low density lipoprotein triglycerides. However, lesion area was only weakly correlated with plasma cholesterol and triglycerides, 0.35 and 0.44 tau values, respectively (P < 0.01). In summary, in the apolipoprotein E-deficient mouse 17-beta-estradiol protects against atherosclerotic lesion formation, and this can only be partially explained through effects on plasma lipoprotein levels.